FASHION TRENDS IN MOLDOVA – THROUGH THE PRISM OF THE CREATIVITY OF YOUNG DESIGNERS - Symak, A.; Babina, Y. (Art and Design, 2018)
The objective of this study is to review and systematize the artistic and stylistic features of the collections of students of the «Fashion Design» specialty of the Faculty of Fine Arts and Design of Ion Creangă State Pedagogical University in the context of expanding the ethno cultural space and preserving the folk traditional culture of Moldova. The methods of comparative analysis, systematic approach, the critical analysis of publications on selected topics, analytical processing and systematization of the collected information base of the study with photo-illustrative material are used in the paper. The collections of young Moldavian designers, the graduates of Ion Creangă State Pedagogical University in Chisinau, have been analyzed; conceptual trends in the modern art of design and fashion in the country, which are based on the individual creative interpretation by young designers of artistic images, have been researched. The significance of the incorporation of folk motives and elements of the culture of Moldova in the work of designers is highlighted. Thus, there is an active interrelation between the traditionalism and modernity, authenticity and global trends; every day, historical, stage/festive and popular Moldavian costume in modern trends in the clothing design of the Republic of Moldova. It was determined that, in addition to the ethno-collections, collections in vintage and dandy styles are also relevant, as well as the embodiment of story-lines and characters from fairy tales, myths, and legends of Moldova when creating collections. It is shown that the Moldavian fashion industry, as the art of fashion design, is at the sufficiently high level and is actively developing, giving preference to the revival of the cultural heritage of the country. The current trends in the development of the fashion market in the Republic of Moldova are determined on the basis of the analysis of creative clothing collections by young designers, graduates of the Faculty of Fine Arts and Design of «Ion Creangă» State Pedagogical University. The research results contribute to creating a more holistic picture of the priorities in modern clothes design in Moldova. In practice these studies can be used in the process of teaching the disciplines of the artistic and aesthetic cycle, mainly in modeling/designing costumes, as well as enriching the professional experience of young designers.